COMMUNITY POLICING IMPLEMENTATION IN THE REPUBLIC OF SERBIA: A VIEW FROM THE MANAGERS’S PERSPECTIVE: CURRENT SITUATION AND POSSIBILITY FOR IMPROVEMENT - Milidragović, Dragan; Milić, Nenad; Dragović, Nebojša (NBP. Nauka, bezbednosti, policija, 2020)
Activities aimed at bringing the police closer to the local community and promoting the building of partnerships and common solutions to security problems are referred to as community policing. In the Republic of Serbia, community policing implementation formally started in 2003 through the ‘Community Policing’ project. After the initial period of implementation, community policing principles were expected to become part of the organizational culture of police organization and a distinctive feature of everyday police practice. Based upon research results presented in this paper, authors sought to determine to what extent the concept of community policing came to fruition in Serbian police practice and how it works today.The research was directed towards the middle management of the Serbian police, where the sample included all regional police departments in Serbia. The paper concluded that at the time this research was conducted, community policing was not sufficiently implemented in the Serbian police practice, that reactive work still dominated over prevention and proactive work, the organizational structure did not allow greater representation of CP activities, there was a need for additional training of police officers and the legislation which could facilitate partnership between the police and the community was missing.
Keywords: police reform, crime prevention, partnership, community policing officers, problem solving, organizational changes.